2008
DOI: 10.1111/j.1365-2672.2007.03633.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination and outgrowth of Bacillus subtilis and Bacillus licheniformis spores in the gastrointestinal tract of pigs

Abstract: Aims:  To determine if orally ingested Bacillus spores used as probiotics or direct‐fed microbial feed additives germinate and the vegetative cells grow in the gastrointestinal (GI) tract. Methods and Results:  Three independent experiments were done to determine if spores of Bacillus licheniformis and Bacillus subtilis germinate and grow in the GI tract of pigs. After a 2 weeks spore‐feeding period, spores were detected in all segments of the GI tract. The lowest number of spores was found in the stomach, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 33 publications
2
91
0
Order By: Relevance
“…Probiotic preparations belonging to single or multispecies of Lactobacillus, Streptococcus, Bacillus, Bifidobacterium, Enterococcus, Aspergillus, Candida, and Saccharomyces had a potential effect on modulation of the intestinal microflora and pathogen inhibition (Kabir, 2009). This could be owing to the production of antimicrobial substances such as bacteriocins and lactic acid, and the adherence and co-aggregation of probiotic bacteria to the mucosa, forming a barrier that prevents colonization by pathogens (Patterson & Burkholder, 2003;Leser et al, 2008). The antimicrobial activity of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic preparations belonging to single or multispecies of Lactobacillus, Streptococcus, Bacillus, Bifidobacterium, Enterococcus, Aspergillus, Candida, and Saccharomyces had a potential effect on modulation of the intestinal microflora and pathogen inhibition (Kabir, 2009). This could be owing to the production of antimicrobial substances such as bacteriocins and lactic acid, and the adherence and co-aggregation of probiotic bacteria to the mucosa, forming a barrier that prevents colonization by pathogens (Patterson & Burkholder, 2003;Leser et al, 2008). The antimicrobial activity of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, spore germination has been observed in the GI tracts of pigs, using flow cytometry analysis (17). While all of these findings are important in the context of mammalian hosts, it cannot be assumed that they will translate directly to an avian host, primarily due to differences in GI anatomy and physiology.…”
mentioning
confidence: 99%
“…Under the experimental conditions used, maximal fiber release was observed after 16-20 h. The transit time in the small intestine is normally estimated to be less than 7 hours (Strube et al 2013). Conversely, Leser and co-workers found a substantial amount of vegetative Bacilli in the caecum of pigs 24 h after administration of two strains of B. subtilis and B. licheniformis (Leser et al 2008). While it is not possible to directly extrapolate the kinetics from our simple in vitro system to the conditions in the GI tract in the piglet, our data suggest the possibility that the strains of B. mojavensis, when co-fed with potato pulp as a feed supplement, could release prebiotic fibers in the small intestine.…”
Section: Discussionmentioning
confidence: 97%
“…Whether Bacillus spores are capable of readily germinating and growing in the GI tract has not been unequivocally proven, but it has been suggested that some of the probiotic effects of Bacillus species might be attributed to the spore itself (Leser et al 2008;LaTorre et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation